2004
DOI: 10.1615/critrevneurobiol.v16.i4.30
|View full text |Cite
|
Sign up to set email alerts
|

Morphinan Neuroprotection: New Insight into the Therapy of Neurodegeneration

Abstract: Neuro-inflammation plays a pivotal role in numerous neurodegenerative disorders, such as Parkinson's disease (PD). Traditional anti-inflammatory drugs have limited therapeutic use because of their narrow spectrum and severe side effects after long-term use. Morphinans are a class of compounds containing the basic morphine structure. The following review will describe novel neuroprotective effects of several morphinans in multiple inflammatory disease models. The potential therapeutic utility and underlying mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…Increasing evidence from both in vivo and in vitro studies suggest that morphinans possess important immunomodulatory potential (62). Morphinans are a group of compounds structurally similar to morphine, but lacking the E-ring found in the naturally occurring opioids, as well as the 6-OH and the 7,8-double bond.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence from both in vivo and in vitro studies suggest that morphinans possess important immunomodulatory potential (62). Morphinans are a group of compounds structurally similar to morphine, but lacking the E-ring found in the naturally occurring opioids, as well as the 6-OH and the 7,8-double bond.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies and those of others have shown that these compounds work at very low concentrations, to inhibit both cellular activation and microglial cell-mediated neurotoxicity. More importantly, the dextrorotatory form of this compound, which has no affinity or effect on the mi-opioid receptors and therefore does not cause addiction, is equally if not more effective than its l form in mediating anti-inflammatory effects on microglia (62). Given the effectiveness of these compounds at such low concentrations and the broad spectrum of activity in inhibiting inflammatory responses, these compounds appear to have significant potential in the treatment of chronic inflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that several analogs of morphinans, such as naloxone, naltrexone or dextromethorphan are potent anti-inflammatory and neuroprotective compounds (Zhang et al 2004). Naloxone and naltrexone are non-selective antagonists of the G-protein-coupled opioid receptors.…”
Section: Therapies Using Morphinan-related Anti-inflammatory Compoundmentioning
confidence: 99%
“…These compounds include IL-10 [95, 96], TGF β 1 [97, 98], morphinan derivatives [99], and DPI, an inhibitor of oxidative stress responses [100]. It is well known that while these compounds have numerous regulatory effects on multiple biological targets, one of their primary anti-inflammatory features is the inhibition of NF- κ B within macrophages and microglial cells [101].…”
Section: Nf-κb and Da Neuroinflammationmentioning
confidence: 99%